Dyslipidemia Associated with Hypertension Increases the Risks for Coronary Heart Disease: A Case-Control Study in Harapan Kita Hospital, National Cardiovascular Center, Jakarta. (30th April 2019) - Ariyanti, Rea; Besral, Besral
Abstract : Background. Coronary Heart Disease (CHD) is the main highlight of the major cardiovascular diseases. In Indonesia, CHD is the leading cause of death from all deaths, with rates reaching 26.4%, which is four times greater than cancer mortality rates. Objective. This study aims to determine whether dyslipidemia associated with hypertension increases the risks for the incidence of CHD in Harapan Kita Hospital, National Cardiovascular Center, Jakarta, or does not. Methods. The study design was case control. The sample was 163 respondents, 82 respondents in the case group and 81 respondents in the control group. The data were analyzed by using logistic regression. Results. In the CHD group, the percentage of respondents with dyslipidemia was 50%, while in the control group, the percentage of respondents with dyslipidemia was 17.3%. The relationship of dyslipidemia with the incidence of CHD differed according to hypertension status. After being controlled for age, in hypertensive respondents, those with dyslipidemia was 18.1 times more likely to develop CHD compared with those nondyslipidemic, whereas in nonhypertensive respondents, those with dyslipidemia was 2.5 times more likely to develop CHD compared with those nondyslipidemic. Recommendation. It is recommended that the community have medical checkup regularly and change lifestyles by taking healthy diet to control lipid profile and blood pressure.